Relationship between Flower Opening in Six Cotton Cultivars and Their Progeny to Pollen Dehydration Tolerance. (11th May 2017) - Burke, John J.; Ulloa, Mauricio
Abstract : Cotton ( Gossypium hirsutum L.) production in arid and semiarid environments routinely experiences elevated temperature and low humidity challenges that ultimately determine yield and producer profitability. The present study investigated the diversity of flower petal opening to determine if traditional genetics and breeding approaches could develop a more cupped or closed flower, thereby providing a more humid microenvironment around the dehisced pollen. Six cultivars with reported differences in pollen humidity sensitivity were used to evaluate the genetics of petal opening. Crosses between open flower cultivars generally resulted in F1 offspring with open flowers. Crosses between closed flower cultivars generally resulted in F1 offspring with closed flowers. Crosses between open and closed flower cultivars provided unique phenotypes depending on the cultivars used. The results from the F1 offspring suggested that the male parent influenced the flower shape of the offspring. In addition, analysis of F2 offspring from the bidirectional crosses suggests that a single dominant gene from the male parent ultimately influences flower petal openness. Using traditional breeding techniques, it may be possible to develop cultivars with either open or closed flower phenotypes, linking pollen development stability and mature pollen viability across a range of environments to stabilize and enhance crop yield.